Improving Learning Motivation of Natural-Social Science Learning Through Game-Based Learning Utilising Quartet Cards - Pradita, Ayu Surya; Nisa, Ana Fitrotun; Masjid, Akbar Al; Cahyani, Berliana Henu (FKIP Universitas Lampung, 2024)
Objective: This research aims to determine the effect of using the game-based learning (GBL) model on fostering learning motivation in natural-social sciences (IPAS) learning. The use of the game-based learning model can serve as an alternative in innovative learning activities. Method: The method used in this research is a quasi-experimental method with a quantitative approach. This research uses a one-group pre-test and post-test design. The subjects in this study are 24 third-grade students at SD Negeri 2 Danguran. The data analysis technique used is the